2015
DOI: 10.1002/oti.1402
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nature of the Intention, Meaning and Perception Process of the Neuro‐occupation Model to Understand Adaptation to Change

Abstract: The theoretical model of neuro-occupation, intention, meaning and perception, sought to describe the symbiotic relationship between occupation and the brain, as a chaotic, self-organized, complex system. Lack of evidence has limited its applicability to practice. The aim of this study was to track the postulates of the model within the daily experiences of subjects. Structured matrices were created for content analysis, using a qualitative multiplecase-study design, typically used for testing models. An underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This finding supports previous qualitative research in which the IMP concepts were presumed to have had theoretically-based relationships [7][8][9]. There are several possible explanations to be considered for this result.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding supports previous qualitative research in which the IMP concepts were presumed to have had theoretically-based relationships [7][8][9]. There are several possible explanations to be considered for this result.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, three qualitative research studies gave credence to the relationships among the IMP variables. One study compared two matched male patients with strokes, both were identified as highly resilient, whereby the findings provided evidence for the proposed relationships among the IMP variables [7]. Subsequently, a study involved comparison of a female with stroke, who demonstrated low resilience behavior, to another female with stroke who demonstrated high resilience behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Further, results of the current study lend support to Champagne, Ryan, Saccomando, and Lazzarini’s (2007) case study in which a young female with symptoms of mania and alcoholism, who was unable to care for her child, was perturbed by fear of being abandoned by her 4-year-old daughter, leading to more enhanced occupational participation. Following this position, the study by Derakhshanrad et al (2016) showed that perturbations provided by social context, such as a family member, occupational therapist, or physical therapist, may have led to enhanced occupational participation in two participants who have had the lived experience of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…(Lazzarini et al, 2004; Derakhshanrad et al, 2015). It seems that performing desired activity can affect quality of life and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It shows the non-linear nature in order to justify the relationship between the nervous system and the participation of people in occupation. Neuro-occupation is interdependent relationship between brain, nervous system and intention to restore or seek meaningful occupation (Derakhshanrad et al, 2015; Gutman and Biel, 2001). …”
Section: Introductionmentioning
confidence: 99%